Financing Policy and Management of Technical Education -An Analysis - Kaur, Harpreet; Bhola, Lovely (Gyan Management Journal, 2018)
Education system plays a key role in economic development. It has been proved empirically as a vital factor of socio-economic development and expenditure on education has been considered as an investment on human resource development (Natarajan, 1993). Education is one of the dominant sectors of the Indian economy in terms of enrollment of children, employment of adults and investment of financial resources (Varghese, 2000). The economy would become more productive if the education system is good. The education system in India has made significant expansion in terms of students enrollment and number of institutions.
Keywords: Education; economic; development; investment; productive